A facile, alternative and sustainable feedstock for transparent polyurethane elastomers from chemical recycling waste PET in high-efficient way. (1st January 2023) - Pu, Mengyuan; Zhou, Xing; Liu, Xiaohui; Fang, Changqing; Wang, Dong
Graphical abstract: Highlights: The feedstock from waste PET can be directly used in 100 % for synthesizing PU. PU developed by a synergistic molecular design in the soft and hard segments. PU elastomer exhibited excellent optical transparency of near 90% The PU can be stretched up to 670% and directly return to the original size. Abstract: Polymers with excellent optical and mechanical performance fabricated from renewable resources, have been paid an increasing attention in recent years. Here, high-performing polyurethane elastomers with significant mechanical properties, crystallinity, excellent stretchability and good transparency are prepared by a synergistic molecular design in the soft and hard segments. Using the liquid glycolysis degradation product (LGOP) as a chain extender, polyurethane elastomer is synthesized from polyethylene terephthalate (PET) waste bottles. The results suggest that the degradation products from waste PET can be directly used as feedstock for preparing polyurethane elastomers with significant performance. The polyurethanes exhibited excellent optical transparency of near 90%, and can be stretched up to 670% without any treatment to return to original size. It is assumed that the symmetrical hard domain composed of aromatic rings and ester groups in LGOP creates sufficient chain fluidity for the dynamic exchange of hydrogen bonds and urethane. This paper has devoted to achieve a complete and mature system from waste PET to polyurethane products, to create a closed loop of waste PET plastic recycling and regeneration, and to realize the polyurethane industrial chain of raw material self-supply.